Comparison of Clinical Outcomes Among Patients With Atrial Fibrillation or Atrial Flutter Stratified by CHA(2)DS(2)-VASc Score - Lin, Yu-Sheng (JAMA Netw Open, 2018)
IMPORTANCE: Current guidelines support treating atrial fibrillation (AF) and atrial flutter (AFL) as equivalent risk factors for ischemic stroke stratified by CHA(2)DS(2)-VASc scores, recommending anticoagulation therapy for patients with a CHA(2)DS(2)-VASc score of 2 or higher, but some studies found differences in clinical outcomes. OBJECTIVE: To investigate differences in clinical outcomes among AF, AFL, and matched control cohorts. DESIGN, SETTING, AND PARTICIPANTS: This nationwide cohort study analyzed data from the Taiwan National Health Insurance Research Database from January 1, 2001, through December 31, 2012. Follow-up and data analysis ended December 31, 2012. A total of 219 416 age- and sex-matched individuals participated in the study. Clinical outcomes were compared after stratification by CHA(2)DS(2)-VASc score (possible score range, 0-9; higher scores indicate greater risk of ischemic stroke). MAIN OUTCOMES AND MEASURES: Ischemic stroke, heart failure hospitalization, and all-cause mortality among the AF, AFL, and matched control cohorts were analyzed using Cox proportional hazards regression. RESULTS: This study comprised 188 811 patients in the AF cohort (mean [SD] age, 73.8 [13.4] years; 104 703 [55.5%] male), 6121 patients in the AFL cohort (mean [SD] age, 67.7 [15.8] years; 3735 [61.0%] male), and 24 484 patients in the matched control cohort (mean [SD] age, 67.3 [15.6] years; 14 940 [61.0%] male). The patients with AF were older, were more predominantly female, and had higher CHA(2)DS(2)-VASc scores than the patients with AFL and the control participants. After stratification by CHA(2)DS(2)-VASc score, the incidence densities (IDs; events per 100 person-years) of ischemic stroke (AF cohort: ID, 3.08; 95% CI, 3.03-3.13; AFL cohort: ID, 1.45; 95% CI, 1.28-1.62; controls: ID, 0.97; 95% CI, 0.92-1.03), heart failure hospitalization (AF cohort: ID, 3.39; 95% CI, 3.34-3.44; AFL cohort: ID, 1.57; 95% CI, 1.39-1.74; controls: ID, 0.32; 95% CI, 0.29-0.35), and all-cause mortality (AF cohort: ID, 17.8; 95% CI, 17.7-17.9; AFL cohort: ID, 13.9; 95% CI, 13.4-14.4; controls: ID, 4.2; 95% CI, 4.1-4.4) were significantly higher in the AF cohort than in the matched control cohort. For the AFL cohort vs the matched control cohort, the incidences of heart failure hospitalization and all-cause mortality were significantly higher across all levels, but the incidence of ischemic stroke was only significantly higher at CHA(2)DS(2)-VASc scores of 5 to 9. For the AF cohort vs the AFL cohort, the incidences of ischemic stroke and heart failure hospitalization were significantly higher at a CHA(2)DS(2)-VASc score of 1 or higher, but the incidence of all-cause mortality was significantly higher only at CHA(2)DS(2)-VASc scores of 1 to 3. CONCLUSIONS AND RELEVANCE: This study found different clinical outcomes between patients with AFL and AF and those without AF and AFL. The current recommended level of the CHA(2)DS(2)-VASc score in preventing ischemic stroke in patients with AFL should be reevaluated.